1998
DOI: 10.1016/s1350-4177(98)00019-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liquid-phase properties on ultrasound intensity and cavitational activity

Abstract: The intensity of ultrasound is attenuated due to various properties of the liquid, such as viscosity, density, etc. In this paper, a simple method is proposed to measure the combined attenuation and cavitational activity of ultrasound intensity in various organic liquids using standard KI decomposition reaction. A modified experimental attenuation coefficient is proposed and its dependence on liquid viscosity reasonably matches the theoretical predictions made by Stokes [G.G. Stokes, Trans. Camb. Philos. Soc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 1 publication
4
25
0
Order By: Relevance
“…Due to geometrical spreading, the acoustic pressure generated by an acoustic transducer drops with increasing distance from the transducer surface [36]. Studies at EKOS, consistent with other studies, have shown that USenhanced thrombolysis is dependent on acoustic pressure generated by transducer [37, 38].…”
Section: Discussionmentioning
confidence: 69%
“…Due to geometrical spreading, the acoustic pressure generated by an acoustic transducer drops with increasing distance from the transducer surface [36]. Studies at EKOS, consistent with other studies, have shown that USenhanced thrombolysis is dependent on acoustic pressure generated by transducer [37, 38].…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, the dependence of cavitation threshold on viscosity demonstrated in the present work ( Figure 5) has confirmed the results of the previous theoretical study [11], which predicts that the cavitation threshold increases with growing viscosity. On the other hand, it has been shown [12] that attenuation of the ultrasound is dependent on viscosity. However, the attenuation of the effects of ultrasound in the EECA is insignificant considering distance of ultrasonic transducer from the source of ultrasound because EECA is much less viscous than oils used in the previous study [12].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been shown [12] that attenuation of the ultrasound is dependent on viscosity. However, the attenuation of the effects of ultrasound in the EECA is insignificant considering distance of ultrasonic transducer from the source of ultrasound because EECA is much less viscous than oils used in the previous study [12]. This method could be robust if an appropriate algorithm for the evaluation of increasing noise-voltage is developed.…”
Section: Resultsmentioning
confidence: 99%
“…Only a small fraction of the total liquid volume in the immediate vicinity of the ultrasound source experiments the effects of cavitation. The intensity of ultrasound is continuously attenuated by the molecules present in the liquid due to various cohesive forces acting on the liquid 16 . The ultrasonic intensity profile in the baths depends entirely on the design and location of the transducers.…”
Section: Introductionmentioning
confidence: 99%
“…A great variety of techniques for the measurement of ultrasonic or cavitation intensity has been listed in the literature 18 , such as chemical reactions 19 , elastic sphere radiometry 20 , aluminium foil erosion 21 , calorimetric and optical methods 16,19,22 , thermoprobes 21 and others 18,23 .…”
Section: Introductionmentioning
confidence: 99%